General Beltrami equations and BMO - Bojarski, B.V.; Gutlyanskii, V.V.; Ryazanov, V.I. (Український математичний вісник, 2008)
We study the Beltrami equations ∂f = μ(z)∂f + ν(z)∂f under the assumption that the coefficients μ, ν satisfy the inequality |μ| + |ν| < 1 almost everywhere. Sufficient conditions for the existence of homeomorphic ACL solutions to the Beltrami equations are given in terms of the bounded mean oscillation by John and Nirenberg.